The Effectiveness of Information System in Public Complaint Service: An Implementation of E-Government Based on Jakarta Smart City Applications (Global Journal of Management and Business Research, 2016)
Public service has a central role in many aspects of human life, and also as the functions in maintaining the existence and growth of the community, the nation and the state. As a capital city of Indonesia, Jakarta is the highest population level of urbanization that make the city face the big problems, such as energy, environment, security, and bureaucracy. In the era of digital government, smart city program become a solution to solve the problems, especially in public service. Smart city is an innovative city and has ability to manage the resources by utilizing ICT to improve public service become more effective, efficient and sustainable. Qlue and CROP are integrated applications of Jakarta Smart City Program that can accommodate all complaints reported by citizens. Furthermore, this paper used descriptive research method with qualitative approach. This study aims to finding out the implementation of e-government and the achievement an effective public service through Qlue and CROP.
Keywords: e-government; jakarta smart city applications; effective public complaint service